Decentralizing public sector collective bargaining and the contradictions of federal practice in Nigeria (2002)
Economic reforms and the quest for efficiency in public administration call for the decentralization of collective bargaining and wages in the public sector in Nigeria. But the effort to decentralize has translated into both a protracted industrial relations crisis and intergovernmental conflict. This situation is traced to the failed effort at institutionalizing collective bargaining and the consolidation of the unified wage structure in the public sector by the resort to ad hoc wages commissions. The distorted fiscal federalism and intergovernmental relations under the military in Nigeria complicated the situation, such that resolving the federal question has become critical to returning stability to Nigeria’s industrial relations system.